Designing modular product architecture using clustering analysis : A printing machine case study - Kongsin, Tanongsak; Janthong, Nattawut (Thai Industrial Engineering Network Journal, 2015)
The mechanical design is necessary to simply modify equipment parts for responding various customer’s demands. Maintenance process, up-grading, replacement, product and modular part design are the general basics of mechanical design. The complicated effects occur while manufacturing process and maintenance process. Clustering analysis that divided into two parts used for studying the suitable process by the concept of this analysis in the clustering of module from the relationship between each part by means of Jaccard method and an item in the cluster is defined by the length between each part for grouping the product architecture following k-means method. The printing machine is used in a case study to demonstrate the analysis trends of modular part and product architecture.